2020
DOI: 10.1515/bot-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

The seaweed resources of Peru

Abstract: The coast of Peru (3.5–18°S) is one of the most productive marine areas in the world. The updated seaweed checklist reports a total of 260 specific/intraspecific taxa, of which the Rhodophyta show the highest number (185 species), followed by Chlorophyta (41 species) and Phaeophyceae (34 species). Since 2012, an increase in molecular studies has been reported mostly in Rhodophyta, while Chlorophyta and Phaeophyceae have lagged far behind. Utilization of seaweed resources has been based on artisanal collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
14
0
3
Order By: Relevance
“…), es evidente que esta es excedida notoriamente por la diversidad de la provincia de Galápagos (321 spp. ;Avila & Padilla, 2020;fig. 14).…”
Section: Similitud De Bray Curtisunclassified
See 1 more Smart Citation
“…), es evidente que esta es excedida notoriamente por la diversidad de la provincia de Galápagos (321 spp. ;Avila & Padilla, 2020;fig. 14).…”
Section: Similitud De Bray Curtisunclassified
“…; Avila-Peltroche y J. Padilla-Vallejos, 2020). La mayor diversidad de las Galápagos está explicada por el elevado nivel de endemismo producto de procesos evolutivos que se intensifican en islas, sin embargo, también hay que considerar que las investigaciones taxonómicas de la flora marina no se han producido con la misma intensidad en la costa de Ecuador y que su conocimiento aún está en una fase más temprana de construcción en esta región (fig.…”
Section: Conclusionesunclassified
“…More recent work has found that a 10-ha cultivation system with M. pyrifera priced at EUR 72/wet tonne would be profitable [ 33 ] Macrocystis pyrifera was only cultured in Peru, with Chile the predominant country for wild harvest collection followed by the US. Peru has one of the most productive marine coastlines in the world, with over 34 recognised brown seaweeds found there; 4% of annual seaweed biomass landings in Peru are produced through seaweed farms, yet this has been declining since 2012 [ 34 ]. The US has used M. pyrifera harvested off the Californian coast as a source of alginate since at least 1913; the harvests have varied from 325,157 wet tonnes in 1918, to 214 tonnes in 1931, to 90,718 in 1984 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular evidence for the introduction of M. japonicus has been shown in Italy [18], the USA, Spain, Australia, and New Zealand [11,22], without reports for South American countries. Even though M. japonicus has not been reported on the Pacific and Atlantic coasts of South America, ten Melanothamnus species have been identified in these regions, with Peru [23][24][25][26]. It is noteworthy to mention that the identification of many of these species, along with the newly identified Rhodophyta species for South America [27][28][29][30][31], was performed thanks to the use of molecular tools, highlighting the importance of molecular analysis for revealing the hidden biodiversity in those regions where the phycological studies have recently begun to increase [25].…”
Section: Introductionmentioning
confidence: 99%